2014
DOI: 10.1155/2014/849623
|View full text |Cite
|
Sign up to set email alerts
|

Micronized Palmitoylethanolamide Reduces the Symptoms of Neuropathic Pain in Diabetic Patients

Abstract: The present study evaluated the effectiveness of micronized palmitoylethanolamide (PEA-m) treatment in reducing the painful symptoms experienced by diabetic patients with peripheral neuropathy. PEA-m, a fatty acid amide of the N-acylethanolamine family, was administered (300 mg twice daily) to 30 diabetic patients suffering from painful diabetic neuropathy. Before treatment start, after 30 and 60 days the following parameters were assessed: painful symptoms of diabetic peripheral neuropathy using the Michigan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 35 publications
1
40
0
Order By: Relevance
“…We also showed that inflammation significantly increased OEA levels in Caco‐2 cells, suggesting that these observations of the pharmacological effects of OEA have a physiologic relevance. Others have similarly shown that OEA is upregulated in response to inflammation (69) or by feeding (70), and this may be as a result of increased OEA synthesis or reduced degradation.…”
Section: Oeamentioning
confidence: 98%
See 1 more Smart Citation
“…We also showed that inflammation significantly increased OEA levels in Caco‐2 cells, suggesting that these observations of the pharmacological effects of OEA have a physiologic relevance. Others have similarly shown that OEA is upregulated in response to inflammation (69) or by feeding (70), and this may be as a result of increased OEA synthesis or reduced degradation.…”
Section: Oeamentioning
confidence: 98%
“…PEA is currently available as a nutraceutical food for medical purposes under the brand names Normast, Pelvilen, and PeaPure; has been studied in humans, mostly within trials on pain management; and is well tolerated (71). Several preclinical animal studies have shown that in vivo treatment with PEA reduces intestinal injury and inflammation via PPARα (47, 48) and also CB 2 and GPR55 (49).…”
Section: Peamentioning
confidence: 99%
“…Case reports and open-label studies suggest an effect of ultramicronized PEA (PEA-um) on neuropathic pain, including central pain [7,12,16,32]. Recent systematic reviews in neuropathic pain and PEA [9,16,36] have only identified 2 randomized placebo-controlled trials, both showing efficacy of micronized PEA (PEA-m) in sciatic pain [6,11].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, PEA treatment significantly reduced the severity and frequency of pain, burning, paraesthesia and numbness. Moreover, the study clearly demonstrated that the analgesic effect manifested itself as early as 30 days after treatment start, progressively increased over time and was maintained 1 month after treatment discontinuation [125].…”
Section: Effect Of Pea On Central and Peripheral Neuropathic Painmentioning
confidence: 76%
“…[124] The results of an open study performed on 30 patients suffering from diabetic neuropathy were recently presented at the 2011 Congress of the European Shock Society. [125] Orally administered PEA (300 mg/twice daily for 60 days) significantly reduced the clinical sensory symptoms (p<0.001), as scored by the Michigan Neuropathy Screening Instrument, Total Symptom Score, and Neuropathic Pain Symptom Inventory. In particular, PEA treatment significantly reduced the severity and frequency of pain, burning, paraesthesia and numbness.…”
Section: Effect Of Pea On Central and Peripheral Neuropathic Painmentioning
confidence: 91%